Fire resistance of lightweight aggregate concrete containing spent garnet as partial fine aggregate replacement - Mohd Faizal, Md Jaafar; Khairunisa, Muthusamy; Nur Farah Aziera, Jamaludin; Sofia Adibah, Jasni; Fahrizal, Zulkarnain (Bentham Science Publishers B.V., 2024)
Introduction: The escalating demand for concrete, driven by global infrastructure development, poses significant challenges to environmental sustainability due to the depletion of natural resources and the accumulation of waste materials. This paper explores the potential of utilizing waste materials, particularly palm oil clinker (POC) and spent garnets, as sustainable alternatives in concrete production. The depletion of natural aggregates, such as river sand, coupled with the environmental hazards associated with waste disposal, underscores the urgent need for eco-friendly solutions in construction materials. POC, derived from palm oil production waste, and spent garnets from abrasive industries offer promising avenues for reducing environmental impact and enhancing sustainability in concrete production. By addressing the dual challenges of resource depletion and waste management, this research aims to contribute to developing greener construction practices and mitigating environmental degradation. Aims: This study aims to investigate the effects of incorporating spent garnet as a partial fine aggregate replacement on the fire resistance of POC LWAC. By examining the interplay between spent garnet inclusion and fire resistance, the research contributes to developing more sustainable concrete formulations and aids in industrial waste management practices, addressing critical societal and environmental challenges. Methods: This study investigates the effects of elevated temperatures on the compressive strength and durability of POC LWAC specimens. Concrete specimens were demoulded after 24 hours of curing and submerged in water for 28 days. Compressive strength and water absorption tests were conducted at the end of the curing period. Subsequently, specimens were subjected to temperatures of 300 °C, 500 °C, and 700 °C for 1 hour in a furnace. After cooling naturally for 24 hours, visual inspection, mass reduction analysis, and evaluation of residual compressive strength were performed. Results: Results indicate that 20% garnet replacement yields the highest compressive strength due to pore filling and denser structure. Higher garnet levels lead to reduced strength and increased water absorption. Visual assessment post-heating shows surface alterations, with 20% garnet exhibiting the lowest mass loss and strength reduction at elevated temperatures. Conclusion: Notably, specimens containing 20% spent garnet in POC LWAC performed better in a fire than others, enhancing their fire-resistant properties. In summary, this research introduces a hopeful approach to improve the sustainability of concrete and mitigate the environmental repercussions of industrial waste